Deformation suffered by the materials that make up the implant-supported overdentures with an increase in the number of implants: from 1 to 4. Bibliographic bibliography - Marcos Moradas Estrada; Beatriz Álvarez López; José María Serrano (Journal of Dental Problems and Solutions - Peertechz Publications, 2018)
A bibliographic review was made on the evidence published in the last 10 years, 2006 - 2016 about the four alternative therapeutic options for a complete prosthesis in a complete mandibular edentulous patient: overdenture on 1, 3 or 4 implants, and with the All on protocol four. For this, one of the main search engines in biomedical sciences was used, such as PubMed, through the library of the Faculty of Medicine and Health Sciences of the University of Oviedo. Throwing a total of 1539 results, that after the different fi lters of year of publication, percentile of the magazine and keywords were limited to 34 articles.